# Evaluate 4(a2 + 2b) – 2b when a = 2 and b = –2

Evaluate 4(a2 + 2b) - 2b when a = 2 and b = –2

## This Post Has 7 Comments

1. senituliii says:

4(2² + 2(-2)) - 2(-2) = 4(4-4) + 4 = 4*0 + 4 = 4

2. hany90 says:

3. qxeenjasss says:

The answers 4, hope it helps

4. KayBJ2005 says:

4

Step-by-step explanation:

; 4(a^2 + 2b) = 4a^2 + 8b...then substitute it onto the bracket

; 4a^2 + 8b - 2b

; 4a^2 + 6b,then substitute with the given values of a and b

; 4(2)^2)+ 6(-2)

; 16 - 12 = 4

5. KayleighMorganhopkin says:

First you simply have to substitute 2 in replace of all the a's, and -2 in replace of all of the b's

4((2)2+2(-2))

Then you want to follow the order of operations, PEMDAS (Parantheses-Exponent-Multiplication-Division-Addition-Subtraction), and multiply within the parantheses.

4(4+(-4))

Next you will add within the parantheses (So add the 4 and -4 together)

4(0)

Lastly multiply

0

Hope this helps!

6. slayybay says:

4

Step-by-step explanation:

7. a1supernut37owozkj says:

4 ( (2)^2 + 2(-2) ) - 2(-2)
4 ( 4 - 4 ) + 4
0 + 4 = 4